2005
DOI: 10.2106/jbjs.e.00211
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Results of Expansive Lumbar Laminoplasty in Patients with Spinal Stenosis

Abstract: The satisfactory results of expansive lumbar laminoplasty were maintained at an average of 5.5 years after surgery. The best indications for the lumbar laminoplasty procedure were young and active patients with central spinal stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The etiology of constriction in the majority of the cases of LSS stem from degenerative ligamentum flavum hypertrophy (46%), listhesis with or without ligamentum flavum hypertrophy (24%), disc with or without ligamentum flavum hypertrophy (22%), and hyperostotic changes (11%). 4 Conventional surgical therapy has relied on laminectomy for LSS decompression, however, there have been reports of high complication rates. Benz et al 5 reported a 40% complication rate in a series of patients 70 years of age or older who underwent lumbar decompression.…”
mentioning
confidence: 99%
“…The etiology of constriction in the majority of the cases of LSS stem from degenerative ligamentum flavum hypertrophy (46%), listhesis with or without ligamentum flavum hypertrophy (24%), disc with or without ligamentum flavum hypertrophy (22%), and hyperostotic changes (11%). 4 Conventional surgical therapy has relied on laminectomy for LSS decompression, however, there have been reports of high complication rates. Benz et al 5 reported a 40% complication rate in a series of patients 70 years of age or older who underwent lumbar decompression.…”
mentioning
confidence: 99%
“…[ 14 15 16 ] In laminoplasty, the dura is covered by the bone; thus, restrangulation by the postlaminectomy membrane does not occur. [ 18 28 29 ] But laminoplasty does not have good results in aged >65 years, myelopathy of >2 year duration, spinal canal stenosis of >60%, and kyphotic cervical spine curvature. [ 17 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…Our technique increased the diameter of spinal canal which enhances neurological recovery because of canal enlargement and improvement in the circulation of the spinal cord and nerve roots. [ 18 28 29 ] The re-stenosis of the spinal canal is supposed to be the most common complication of our technique, but the authors did not encounter it in any patients till date; however, long-term results are still awaited. Other complications reported in the literature, like transient C5-6 root paresis, severe neck pain with or without paresthesias, and under riding of the lamina at the hinged side had not occurred in any of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…The laminectomy is always a standard approach to treat lumbar degenerative disease, but it can damage the posterior structure of lumbar, affect spinal stability, cause backache due to the postoperative scar adhesions, and cause failed back surgery syndrome. According to the clinical follow-up implemented by Kawaguchi et al [10], 10% of patients had spondylolysis. The study of Sen et al [11] suggested that the incidence of failed back surgery syndrome caused by epidural scar adhesion was 8–24%.…”
Section: Discussionmentioning
confidence: 99%